Epidural anaesthesia and long term backache after childbirth. Issue 6742 (7th July 1990) - MacArthur, C; Lewis, M; Knox, E G; Crawford, J S
Abstract : OBJECTIVE--To examine the relation between epidural anaesthesia and long term backache after childbirth. DESIGN--Data from postal questionnaire on morbidity after childbirth sent to women who had delivered in one maternity hospital between 1978 and 1985 were linked to maternity case notes for each woman. SETTING--Maternity hospital in Birmingham. SUBJECTS--11, 701 Women who had delivered their most recent baby at the maternity hospital during the defined period and who returned their completed questionnaires. MAIN OUTCOME MEASURES AND RESULTS--Of the 1634 women who reported backache, 1132 (69%) had had it for over a year. A significant association was found between backache and epidural anaesthesia (relative risk = 1.8); 903 of 4766 women (18.9%) who had had epidural anaesthesia reported this symptom, compared with 731 of the 6935 women (10.5%) who had not had epidural anaesthesia. This association was consistent in both "normal" and "abnormal" deliveries, the only exception being after an elective caesarean section when no excess backache occurred after epidural anaesthesia. CONCLUSIONS--The relation between backache and epidural anaesthesia is probably causal. It seems to result from a combination of effective analgesia and stressed posture during labour. Further investigations on the mechanisms causing backache after epidural anaesthesia are required.